2022
DOI: 10.3389/fonc.2022.837413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preserving the Pulmonary Vagus Nerve Branches on Cough After Pneumonectomy During Video-Assisted Thoracic Surgery

Abstract: BackgroundCough is one of the most common complications of early-stage non-small cell lung cancer (NSCLC) after video-assisted thoracoscopic surgery (VATS). The vagus nerve plays an important role in pulmonary inflammation and the cough reflex. In this study, we attempted to reduce the incidence of postoperative chronic cough and other complications by preserving the pulmonary vagus nerve branches.Patients and MethodsThis study was a randomized controlled double-blinded trial of subjects and observers. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…fentanyl, sufentanil, remifentanil and alfentanil), are widely used in the induction and maintenance of anesthesia, have been reported to cause the development of postoperative cough [32,33]. Although this study failed to corroborate above risk factors, we did observe that the longer duration of anesthesia may be associated with a greater risk of postoperative cough, in agreement with many previous studies [7,9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…fentanyl, sufentanil, remifentanil and alfentanil), are widely used in the induction and maintenance of anesthesia, have been reported to cause the development of postoperative cough [32,33]. Although this study failed to corroborate above risk factors, we did observe that the longer duration of anesthesia may be associated with a greater risk of postoperative cough, in agreement with many previous studies [7,9].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that the longer duration of anesthesia was a signi cant risk factor of postoperative cough, in agreement with many previous studies [7,9]. It is important to consider factors during anesthesia that may explain this result, such as.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Possible reasons for the increased arrhythmia in S-LND could be the increased extent of resection 33 and manipulation around the vagus nerve branches. 34 , 35 In this analysis, we could not specifically determine the impact of different arrhythmia types because of the limited information available in each study. Future studies concerning this topic would assist in expanding our understanding of the long-term detrimental effect of postoperative arrhythmia in lung surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Approximately 25%-50% of patients presented with short-term postoperative cough. 2 , 3 Short-term cough after lung cancer surgery was more often associated with surgery and anesthesia, such as injury to the vagus nerve or its branches, 4 lymph node dissection, 5 anesthetic drugs, 6 and tracheal intubation. 7 Unlike short-term postoperative cough, some patients may suffer from a persistent chronic cough that persisted beyond the initial recovery period from surgery.…”
Section: Introductionmentioning
confidence: 99%